Operational Model and Treatment Costs of a Student-Run Free Clinic Serving People Who Inject Drugs - Patel, Hardik; Hinkes, Samuel; Mathew, Megan; Castillo, Marcus; Serota, David; Tookes, Hansel (Journal of Student-Run Clinics, 2022)
Background: The student-run Infectious Disease Elimination Act (IDEA) Clinic serves people who inject drugs (PWID) by providing human immunodeficiency virus testing, hepatitis C virus testing, wound care, cutaneous abscess treatment, safe injection education, and basic health screening services. A primary goal of the IDEA Clinic is to prevent the progression of wounds and infections into more severe and costly illnesses. Here, we present the operational model and treatment costs associated with providing these services at the IDEA clinic. Methods: Charts of PWID who received medical care at the IDEA Clinic over a 28-month study period were reviewed and the services provided are reported. Total costs were stratified into the cost of medical equipment, procedures, and medications. Results: From October 2017 to January 2020, the total cost of supplies of the IDEA Clinic totaled 3,491.65. Over this study period, there were 291 distinct patient visits, which gives the clinic an average cost of 12.00 per visit. Conclusions: The IDEA Clinic requires low per-patient operational costs to provide important medical services to a vulnerable population. The results of this study may be used to support the creation of more student-run clinics in other areas with a large population of PWID.